Inventory of Policy, Strategic, and Legislative Instruments for the Transformation of the Livestock Sector in Ethiopia - Michael, Melaku; Kassie, Girma; Haile, Aynalem (Federal Attorney General, 2022)
Over the last three decades, the Government of Ethiopia (GoE) has come up with multiple development plans, policies and strategy documents and legal instruments that intend to transform the agricultural sector in general and the livestock sector in particular. In the past four years, the government’s focus seemed to shift from agriculture based economic transformation to industrialization focused national economic growth, while also recognizing the huge socio-economic potential of the livestock sector. A different set of livestock related policy, strategy and legislative instruments are in effect and a few others are being drafted to guide the contribution of the livestock sector to economic transformation. The livestock sector analysis (LSA), livestock master plan (LMP), and the poultry breeding strategy are few of the prominent policy and strategic documents that aim to reorient the livestock production system in an inclusive manner, to make the smallholder communities beneficiaries of the developments in the sector. Animal Disease Prevention and Control Proclamation No. 267/2002, Veterinary Drug and Feed Administration and Control Proclamation 728/2011, and Live Animals Marketing Proclamation 819/2014 are also other noticeable legislations enacted by the House of People Representatives (HPR) trying to regulate the livestock production industry. The aspiration to transform the livestock production, as indicated in the policy instruments, requires a great deal of legislative intervention that creates conducive environment for increasing animal feed production, availability of animal health service providing institutions, genetic improvement of livestock, and marketing of livestock products. In fact, the legal instruments in effect and those in the pipeline need a long overdue amendment and skillful formulation, respectively, to accommodate and transform the livestock sector agenda. A critical examination shows weak linkage between the policy goals (general aspirations to be realized) and with that of the legislative means that provide the structural and institutional foundation, which in turn facilitate the attainment of the policy goals. The best illustration for this is the formulation of policy and strategy documents precedes the drafting of legal instruments that aim to facilitate the realization of objectives stipulated in the policy documents. Specifically, regarding the livestock sector, most of the legislations enacted by the house of people’s representatives (HPR) or the Council of Ministers precede the recently formulated livestock master plan and breeding strategies. Therefore, any policy and strategy document which aims at transforming the livelihoods of the smallholder rural community requires a legal framework. This framework facilitates the formation of institutional structures and strengthens their capacity to develop the smallholder livestock production focusing on, but not limited to, increasing animal feed production, improving animal health service availability, and enhancing genetic improvement. A legal intervention is also required to kick-start the domestic livestock market by providing an enabling legal framework that facilitates the formation and proliferation of community-based no- or minimum-collateral demanding loan providing financial institutions that encourage smallholder livestock production communities to join the livestock marketing sector and develop livestock-based entrepreneurship skills. Most importantly the legal and institutional frameworks need to establish a self-sustaining, holistic, and expanding livestock market structure.